ANALISA KINERJA BIROKRASI PELAYANAN IMB PADA DINAS PEKERJAAN UMUM KABUPATEN KUTAI TIMUR - Rizaldy, Mohammad (PREDIKSI, 2012)
Execution of passed to service is society in the case of which licensing in its application of society have to deal with organization service of governmental public. Most society meet difficulty because management of the IMB very circumlocutary, Â so that management of inefficient IMB and require time old ones.Target of this Research to know and mendeskripsikan execution of function in management of administrative services of licensing of IMB at On duty Public Work in Sub-Province of Kutai East and to know factor influencing management of administrative services of licensing of IMB at On duty Public Work in Sub-Province of Kutai East.Result of research of menunjukan that Execution Of Function On Duty Public Work Of Area Create Masterpiece Sub-Province of Kutai East in management of administrative services of licensing of Permission Found Building ( IMB) in Sub-Province of Kutai East have run owned function it as according to order going into effect and factor influencing management of administrative services of licensing of IMB in Sub-Province East consist of supplementary factor that is existence of clear order which arrange about IMB, supporter medium and of loyalitas officer to its work. As for resistor factor in management of administrative services of licensing of IMB is the lack of prasarana and lack of awareness of society in equiping conditions in proffering of application of IMB.